2010
DOI: 10.1177/1082013210366885
|View full text |Cite
|
Sign up to set email alerts
|

Screening Filamentous Tropical Fungi for their Nutritional Potential as Sources of Crude Proteins, Lipids and Minerals

Abstract: The use of fungal and yeast biomass in foodstuff, either as supplements or as major ingredients in formulations is an area of growing interest for the modern food industry. The aim of this study was to evaluate the nutritional potential of biomasses obtained from filamentous fungi Penicillium sclerotiorum, Penicillium janthinellum, Rhizopus stolonifer and Syncephalastrum racemosum. Biomasses presented 26-37% of total proteins, 1.7-3.5% of lipids and 4.6-9.1% of ashes. The humidity level reached 75-83%. Ashes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
1
1
1
Order By: Relevance
“…The lower values reported for the CF and the fibre fractions may be due to the hydrolytic nature of the fungi species, which could have delignified the lignocelluloses complex and utilised them by microbes during fermentation thus converting them to more useful components like protein or NFE. This conforms with the report of Carvalho et al 27 that enzymes from most fungi can improve not only the non-starch polysaccharides but also the crude proteins, minerals and fatty acids. Akinfemi et al 4 , Barde et al 20 and Ochepo 21 have earlier reported improved ash values on agro by-products degraded using Pleurotus spp.…”
Section: Resultssupporting
confidence: 93%
“…The lower values reported for the CF and the fibre fractions may be due to the hydrolytic nature of the fungi species, which could have delignified the lignocelluloses complex and utilised them by microbes during fermentation thus converting them to more useful components like protein or NFE. This conforms with the report of Carvalho et al 27 that enzymes from most fungi can improve not only the non-starch polysaccharides but also the crude proteins, minerals and fatty acids. Akinfemi et al 4 , Barde et al 20 and Ochepo 21 have earlier reported improved ash values on agro by-products degraded using Pleurotus spp.…”
Section: Resultssupporting
confidence: 93%
“…oryzae biomass produced in SSL (60%) (Asadollahzadeh et al, 2018). Carvallo et al (2010) found a much lower Ca content (4.90±0.30 and 258.40±2.28 mg/100gm) of different filamentous fungi than the present study. The contents of Zn and Fe of the present study were much higher than those found in the biomass of different filamentous fungi reported by Carvallo et al (2010).…”
Section: Discussioncontrasting
confidence: 75%
“…The presence of in A. niger ‐SCP indicated that it was a good choice as a feed supplement as vitamin A is required for fish growth and development. A few studies were reported on the vitamin B complex content of fungal SCP (Adedayo et al, 2011) and filamentous fungi (Carvallo et al, 2010). To the best of the existing knowledge, for the first time, vitamin A, D 2 , D 3 and E of A. niger ‐SCP from whey were reported.…”
Section: Discussionmentioning
confidence: 99%